Allegories of Immersion - Filippo Fimiani (AN-ICON, 2023)
Fish Night, an episode of LOVE DEATH + ROBOTS (S01E12, 2019) based on a 1982 short story by Joe R. Lansdale, can be interpreted as an allegory of the impossibility of immersive experience: if real, it is deadly, because the images are no longer such or ghosts but living beings present in a shared environmental habitat, acting with but also against the subject, in turn no longer a spectator. Comparing the story and film, and ancient ekphrastic literature, I discuss, in a trans-medial imaginary genealogical perspective, the symptoms of this cultural topos and of the regressive desire for immersion and for transparent immediacy that shapes and drives it, dwelling in particular on the ambivalent phenomenological and ontological relations between living bodies, pictures and media as deep time-bending.